(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the effec of increasing cerebral blood flow of extra Buyang Huanwu liquid extract in mice. Subjects and methods: Experimental study, using the mouse model of chronic cerebral hypoperfusion by bilateral common carotid artery stenosis. Results: Buyang Huanwu extract at the doses of 49,8g/kg/day and 149,4g/kg/day increased cerebral blood flow on mouse model of chronic cerebral hypoperfusion by bilateral common carotid artery stenosis at the time 14 days and 28 days after surgery. Conclusions: The extra Buyang Huanwu extract with the doses of 49,8g/kg/day and 149,4g/ kg/day increased cerebral blood flows on mice similar to that of Ginko Biloba dose of 100 mg/ kg day